Artificial Intelligence Assisted Learning in Primary Education: Examining Its Impact on Critical Literacy, Learning Engagement and 21st Century Skills Development - Muh Habibulloh (J-PE: Jurnal Pendidikan, 2026)
Artificial Intelligence (AI) has emerged as a transformative force in education, offering innovative opportunities to enhance learning experiences, promote personalized instruction, and develop future-ready competencies. Despite the growing integration of AI technologies in educational settings, empirical evidence regarding their effectiveness in primary education, particularly in rural and semi-rural contexts, remains limited. This study investigates the impact of AI-assisted learning on critical literacy, learning engagement, and 21st-century skills among elementary school students in Trenggalek Regency, Indonesia. Employing a mixed-method quasi-experimental design, the study involved 128 fifth-grade students from four public elementary schools: SD Negeri 1 Surodakan, SD Negeri 2 Baruharjo, SD Negeri Sumbergayam, and SD Negeri 1 Kedung Lurah. The intervention was implemented over twelve weeks and integrated ChatGPT-assisted inquiry learning, AI-supported reading activities, adaptive quizzes, AI-generated project tasks, and automated feedback systems. Quantitative data were collected through critical literacy tests and student engagement questionnaires, while qualitative data were obtained through classroom observations and semi-structured interviews. Statistical analyses included descriptive statistics, independent-sample t-tests, and effect size calculations, whereas qualitative data were analyzed using thematic analysis. The results revealed that students exposed to AI-assisted learning achieved significantly higher critical literacy scores (M = 82.40) than students receiving conventional instruction (M = 71.60), with a large effect size (d = 1.76). Furthermore, AI-assisted learning significantly improved behavioral, emotional, and cognitive engagement, while also fostering digital literacy, critical thinking, creativity, communication, collaboration, and problem-solving skills. Qualitative findings indicated increased learning motivation, personalized support, and enhanced inquiry behaviors. These findings suggest that AI-assisted learning represents an effective pedagogical innovation capable of strengthening literacy development, student engagement, and future-oriented competencies in primary education, particularly within rural educational contexts undergoing digital transformation.